Between Trust and Suspicion: A Comparative Study of the Relationship between Politicians and Political Journalists in Belgium, Norway and Sweden - Van Aelst, Peter; Aalberg, Toril (Javnost-The Public, 2011)
This article presents an empirical study of the relationship between politicians and journalists in three European countries. Based on a survey among political journalists and Members of Parliament in Belgium, Norway and Sweden we ask how “intimate” the relationship between these two groups really is, and if the informality of the relationship also influences the image they have of one another. Our study shows that the degree of informality differs significantly between the three countries, where the Swedes have less informal contact. We believe this country difference can be mainly attributed to the higher degree of political professionalisation. Unlike Nimmo (1964) our analysis does not suggest that the more informal the relationship is, the less suspicious journalists or politicians are towards the other group. Rather our results seem to show that trust and suspicion go hand in hand.